« La nuit, les colleurs se tapent l’affiche » - Bryan Muller (Temporalités)
Nowadays, political parties and trade unions communicate primarily during the day in order to make themselves heard by as many people as possible. This was not always the case. At the height of the Cold War, activists often had to operate at night to promote and defend their ideas - even if it meant exposing themselves physically to reprisals from their opponents. After the war, political communication often favoured (non-)contradictory night meetings, sometimes with incidents. It was only gradually with the technicalisation of communication and the distancing of bodies that physical violence was to recede to the political margins. The trade unions, which were closely linked to political organisations, followed the same pattern, although the decline in night-time physical violence began more quickly and was replaced by controlled daytime violence. This article examines the evolution of militant political and (to a lesser extent) trade union violence in France between 1947 and 1991, using the example of the right and extreme right.